2008
DOI: 10.3802/jgo.2008.19.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5'-CpG island hypermethylation of the FHIT gene in cervical carcinoma

Abstract: Objective: The abnormal expression of fragile histidine triad (FHIT) gene has been frequently reported in a variety of epithelial malignancies including cervical carcinoma. Furthermore, in a recent study it was proposed that transcriptional inactivation of FHIT, as a consequence of aberrant 5'-CpG island methylation, plays an important role in the carcinogenesis of human cervical carcinoma. The authors sought to determine whether abnormal FHIT transcription occurs in human cervical carcinoma, and if so, whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…Although the aberrant promoter region methylation was a common epigenetic event with lung cancer, combined detection of these genes may vastly improve the positive detection rate of tumors or prognostic judgment Dumitrescu et al, 2012;Vo et al, 2013;Al-Temaimi et al, 2013;Zuo et al, 2013). Several studies showed separately that methylation of CpG islands of FHIT, RASSF1A and RARβ genes has a significant role in the process of lung cancer (range, 20-90%, depending on tumor type), this figure identified the these genes as the most commonly modified gene in human cancers (Ki et al, 2008;Neyaz et al, 2008;Jeong et al, 2013;Liu et al, 2013;Al-Temaimi et al, 2013;Zuo et al, 2013). however, there are only a few studies reporting hypermethylation of combined FHIT, RASSF1A and RARβ genes together in cancers, especially in non-small cell lung cancer (Li et al, 2012;Zuo et al, 2013;Mengxi et al, 2013;Ko et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the aberrant promoter region methylation was a common epigenetic event with lung cancer, combined detection of these genes may vastly improve the positive detection rate of tumors or prognostic judgment Dumitrescu et al, 2012;Vo et al, 2013;Al-Temaimi et al, 2013;Zuo et al, 2013). Several studies showed separately that methylation of CpG islands of FHIT, RASSF1A and RARβ genes has a significant role in the process of lung cancer (range, 20-90%, depending on tumor type), this figure identified the these genes as the most commonly modified gene in human cancers (Ki et al, 2008;Neyaz et al, 2008;Jeong et al, 2013;Liu et al, 2013;Al-Temaimi et al, 2013;Zuo et al, 2013). however, there are only a few studies reporting hypermethylation of combined FHIT, RASSF1A and RARβ genes together in cancers, especially in non-small cell lung cancer (Li et al, 2012;Zuo et al, 2013;Mengxi et al, 2013;Ko et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Methylation is major epigenetic modification in mammal, and changes in methylation patterns play a key role in tumor genesis with humans (Virmani et al, 2000;Dumitrescu et al, 2012;Fiolka et al, 2013). In particular, the promoter CpG island hypermethylation is closely related between inactivation and silencing, resulting in tumor suppressor loss of gene expression and X-chromosome inactivationmay, and affect development of carcinogenesis (Ki et al, 2008;Fiolka et al, 2013;Al-Temaimi et al, 2013). The aberrant promoter region methylation of tumor suppressor genes is associated with mechanism for carcinogenesis (Grote et al, 2006;Neyaz et al, 2008;Dumitrescu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations